2017
DOI: 10.1609/aaai.v31i1.11134
|View full text |Cite
|
Sign up to set email alerts
|

The Opacity of Backbones

Abstract: A backbone of a boolean formula F is a collection S of its variables for which there is a unique partial assignment aS such that F[aS] is satisfiable (Monasson et al. 1999; Williams, Gomes, and Selman 2003).  This paper studies the nontransparency of backbones.  We show that, under the widely believed assumption that integer factoring is hard, there exist sets of boolean formulas that have obvious, nontrivial backbones yet finding the values, aS, of those backbones is intractable.  We also show that, under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Third, natural is in the eye of the beholder; although the election-attack problems used in the result are the standard, natural ones, the election systems used are indirectly specified by the hypothesized sets in (NP ∩ coNP) − P, and so are likely not very natural. And fourth and finally, this entire approach then found application in a different area of AI, namely, the study of backbones and backdoors of Boolean formulas, where it was shown for example that if P = NP ∩ coNP, then search versus decision separations occur for backbones (Hemaspaandra and Narváez 2017a;2017b).…”
Section: Search Versus Decision For Np Problemsmentioning
confidence: 99%
“…Third, natural is in the eye of the beholder; although the election-attack problems used in the result are the standard, natural ones, the election systems used are indirectly specified by the hypothesized sets in (NP ∩ coNP) − P, and so are likely not very natural. And fourth and finally, this entire approach then found application in a different area of AI, namely, the study of backbones and backdoors of Boolean formulas, where it was shown for example that if P = NP ∩ coNP, then search versus decision separations occur for backbones (Hemaspaandra and Narváez 2017a;2017b).…”
Section: Search Versus Decision For Np Problemsmentioning
confidence: 99%
“…Given that our hypothesis is that combinatorial problems provide hard instances of SAT problems, we wish to study these structures closely and determine the role they play in the instances we are interested in. In (Hemaspaandra and Narváez 2017a) we looked at a separation in the complexity of finding a backbone versus that of finding the value to which that backbone must be set in order to find a satisfying assignment. This separation is true under the widely-believed assumption that P = NP ∩ coNP.…”
Section: Backbones and Backdoors In Satisfiabilitymentioning
confidence: 99%
“…A large drawback of SBSes and their variants is that in the general case, the problem of finding such a backdoor is computationally hard. A number of results that fit these issues into the context of Structural Complexity can be found in (Kilby et al 2005;Hemaspaandra and Narváez 2017, 2019. The works (Fichte and Szeider 2011;Gaspers and Szeider 2012a,b,c;Misra et al 2013) demonstrate the relationship between backdoors and basic concepts of Parameterized Complexity.…”
Section: Introductionmentioning
confidence: 97%